Deskripsi Penerapan Pendekatan Saintifik Dalam Pembelajaran Tematik Di Kelas V B SDN 21 Pontianak Barat - Al Huda; Siti Halidjah; Kartono Kartono (Departement of Mathematics Education, 2023)
This research aims to find out how the application of thematic learning using a scientific approach in class V B of SDN 21 West Pontianak, starting from designing a thematic learning implementation plan with a scientific approach, then the implementation of thematic learning with a scientific approach and the obstacles faced by teachers in carrying out thematic learning with a scientific approach scientific. The type of research used in this research is descriptive research with qualitative methods. The source of the data in this study was the class V B teacher at SDN 21 West Pontianak with the resulting data being the result of observing the lesson plan, the result of observing the implementation of the lesson and the results of interviews with the teacher. The results of the study show that the plan for implementing thematic learning with a scientific approach that has been made by the teacher still has deficiencies, namely in the learning objectives section because it is not appropriate and does not include existing competency achievement indicators and is not in accordance with the ABCD formula, then remedial and enrichment activities have not been planned properly, then the core learning activities in the reasoning section are still not well planned. In the implementation of thematic learning with a scientific approach carried out by the teacher, it still tends to be in one direction, reasoning activities have also not been carried out properly, the obstacles faced by the teacher are the limited facilities available in the teacher's school, the difficulty in planning reasoning activities and increasing the curiosity of students because it is based on interviews and observations made by students look passive and less active in participating in the learning process.